An improvement on "Integrated production strategy and reuse scenario: A CoFAQ model and case study of mail server system development". (October 2015) - Wu, Zhiqiao; Tang, Jiafu; Kwong, C.K.; Marinelli, F.
Abstract: The authors (Tang et al. (2013)[1] developed a CoFAQ model to formulate a solution for the problem of production strategy decision and reuse scenario selection for a software product family. In the previous research, we stated that the CoFAQ model was a 0–1 mixed integer nonlinear program, where only a local optimal solution might be found. In a recent study, we found that the CoFAQ could be transformed into a 0–1 mixed integer linear programming model. By solving the model, a global optimal solution can be obtained. In this paper, we present the improved formulation and the optimal solution for the case study. Highlights: A deficiency of the work reported in a published paper is described. The CoFAQ problems can be transformed into linear programming ones. A global optimal solution can be guaranteed for the problems with any scale.